Benefit from adjuvant radiotherapy according to the number of risk factors in cutaneous squamous cell carcinoma. (March 2022) - Pêtre, Adeline; Pommier, Pascal; Brahmi, Tristan; Chabaud, Sylvie; King, Sophie; Fayette, Jérôme; Neidhart, Eve-Marie; Amini-Adle, Mona
Highlights: An increased number of risk factors was identified as being the highest predictive factor of relapse in cutaneous squamous cell carcinoma (cSCC). Adjuvant radiotherapy tends to improve the progression free survival (PFS) in high-risk cSCC. Adjuvant RT significantly improves PFS for high-risk cSCC with ≥3 risk factors. Abstract: Introduction: Indications of adjuvant radiotherapy (RT) for high-risk cutaneous squamous cell carcinoma (cSCC) are not clearly defined. We aimed to identify factors predicting relapse in cSCC patients treated with surgery or RT alone and to assess in which clinical setting adjuvant RT was beneficial in term of progression free survival (PFS). Methods: This retrospective analysis included patients with resectable primary cSCC treated with surgery and/or RT in curative intent, managed at Centre Léon Bérard (Lyon, France) from April 2010 to September 2020. Results: A total of 303 patients with 529 cSCC were included. 31 (5.9%) cSCC were treated with surgery and adjuvant RT. With a median follow-up of 54 (0.2–126) months, 103 (19.5%) cSCC relapsed. In multivariate analysis, the highest predictive factor of relapse in cSCC was the number of risk factors (HR = 15.110 [95% CI: 3.91–58.40] for ≥3 risk factors p < 0.001), followed by poor differentiation (HR = 4.930 [95% CI: 2.47–9.86], p < 0.001) and perineural invasion (HR = 2.442 [95% CI: 1.11–5.38], p = 0.027). For cSCC with ≥3 risk factors, PFS was significantly higher in cSCC treated with surgery and adjuvant RT compared to those treated with surgery or RT alone (the 36-month PFS was 74% [95% CI: 43–90%] and 31% [95% CI: 10–54%] respectively, p = 0.008). Conclusion: An increased number of risk factors was identified as being the highest predictive factor of relapse in cSCC. Adjuvant RT improved PFS for high-risk cSCC with ≥3 risk factors.